y-3=6/5(x-3)

Simple and best practice solution for y-3=6/5(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-3=6/5(x-3) equation:


x in (-oo:+oo)

y-3 = (6/5)*(x-3) // - (6/5)*(x-3)

y-((6/5)*(x-3))-3 = 0

(-6/5)*(x-3)+y-3 = 0

y-6/5*(x-3)-3 = 0

y-6/5*(x-3)-3 = 0

y-6/5*x-3+18/5 = 0

y-6/5*x+3/5 = 0

y-6/5*x+3/5 = 0

y-6/5*x+3/5 = 0 // - y+3/5

-6/5*x = -(y+3/5) // : -6/5

x = (-(y+3/5))/(-6/5)

x = 5/6*(y+3/5)

x = 5/6*(y+3/5)

See similar equations:

| x+20=78 | | 3j^2+19j+16=0 | | 43k^2+27k=0 | | VXYZ/UVXYZ | | -3-17m=54 | | 3-2x-7+3=x-4 | | 5x+6x-2x-5=58 | | -8x-45=15-28x | | 12/1.27 | | -3-2n=-17 | | 10x-4=90 | | 2k+3=6k-4 | | 32+14y=4 | | 8-2(p-6)=52 | | 5/11=p/17 | | 52x^3+13x^4= | | 5u^2+18u+9=0 | | -4+8n=-78 | | 100*0.14*2= | | 4s-10=s+11 | | 3(12-x)=4+5X | | (-2)-9=-11 | | 10n+n^2=72 | | 12-1/3x=18 | | -5x+3=2x+17 | | 6(6)=17 | | 12-(163/15) | | p-4px/p | | 4n+2n=12 | | 3=p+3-1 | | 13b-9=4b-63 | | -18n-30n=-18-10n |

Equations solver categories